Identificación y elaboración de productos turísticos para el cantón Saquisilí. - Luisataxi Galarza, Mishell Katherine (2023)
The developed current research project in the Saquisili canton was made with the aim of developing tourist products, by taking advantage of cultural and natural attractions, what it has, which it has been proposed three aims, into aim one, is was applied the exploratory research, which allowed getting information about the tourist attractions inventory , through field trips and the methodology application from hierarchy of attractions and generation of tourist spaces into Ecuador, where it was applied Stage I, tourist attractions inventory elaboration, what includes two phases, I survey and registration, II weighting and hierarchization, where it was filled out the attractiveness sheets and was validated the data, through a check list, which allowed getting as results, 19 inventoried attractions of which 11 are cultural and 8 natural. For the second aim, it was applied the Tourist Products Planning Manual from Peru, it was used the survey technique to know the tourist profile and, in this way, is gets the product "Saquí - Aventura", considering that 8 attractions distributed into the parishes Canchagua and Cochapamba. For the last aim, it was made a focus group to tourism responsible from canton to get information about the tourism development, later, it was made a FODA and the MEFI and MEFE matrices application, give as result 1 offensive strategy, 1 defensive, 1 reorientation and 1 survival, to later generate an action plan proposal, which integrates activities, managers, budget.